SOCIAL ACTION METHOD AND THE #ENDSARS PROTESTS IN NIGERIA SOCIAL WORK APPROACH - Emerinwe, Obuzor, Mezewo; Nwabueze, Emeodu, Elijah (Journal of Learning on History and Social Sciences, 2025)
Objective: This paper examines the social action method and the EndSARS protest in Nigeria from a social work perspective, with the aim of recommending solutions to address the causes of the protest and police brutality in Nigeria. Method: The study adopts the structural-functionalist theory and utilizes a qualitative approach through survey research. Data was collected from secondary sources, including journal articles, newspapers, and online publications. Results: The findings reveal that the Special Anti-Robbery Squad (SARS) became notorious for its brutality and human rights abuses, with a lack of accountability for its actions. The Nigerian economy also faced significant financial losses during the protests. Furthermore, the Police Act of 1943, which grants broad discretionary powers to police officers, facilitates the abuse of power. Novelty: The paper highlights the global impact of the EndSARS protest, focusing on police brutality in Nigeria. It recommends a multi-stakeholder approach to reform, including engagement with civil society organizations, traditional institutions, and youth employment initiatives, to address systemic issues and foster sustainable development.